Syntheses of Phoyunbenes A‐D and Thunalbene for their Anti‐Inflammatory Evaluation. (30th November 2015) - Moon, Insu; Kim, Jin‐Kyung; Jun, Jong‐Gab
Abstract : Simple and efficient first syntheses of phoyunbenes A‐D and thunalbene have been developed using Horner–Wadsworth–Emmons reaction as a key step. Later, their anti‐inflammatory effects were investigated in lipopolysaccharide‐induced RAW‐264.7 macrophages. The results revealed that phoyunbenes A‐D and thunalbene showed weak inhibitory activities without cytotoxicity on the production of nitric oxide (NO) which is an important inflammatory mediator. Abstract :